Epigallocatechin gallate improves insulin signaling by decreasing toll‐like receptor 4 (TLR4) activity in adipose tissues of high‐fat diet rats - Bao, Suqing; Cao, Yanli; Fan, Chenling; Fan, Yuxin; Bai, Shuting; Teng, Weiping; Shan, Zhongyan (Molecular nutrition & food research, 2014)
SCOPE: In this study, we investigated the beneficial effects and the underlying mechanism of epigallocatechin gallate (EGCG) in adipose tissues of rats fed with a high‐fat diet (HFD). METHODS AND RESULTS: Fasting plasma insulin, epididymal fat coefficient and free fatty acids, homeostasis model assessment‐insulin resistance index, and the average glucose infusion rate were determined. EGCG significantly decreased free fatty acids, fasting insulin, homeostasis model assessment‐insulin resistance index, and epididymal fat coefficient, and increased glucose infusion rate in HFD group. The levels of toll‐like receptor 4, TNF receptor associated factor 6, inhibitor‐kappa‐B kinase β, p‐nuclear factor κB, tumor necrosis factor α, and IL‐6 in the EGCG group were all significantly lower than the HFD control group. EGCG also decreased the level of phosphorylated insulin receptor substrate 1 and increased phosphoinositide‐3‐kinase and glucose transporter isoform 4 in the HFD group. Decreased macrophage infiltration was in EGCG group versus HFD group, and the protein level of CD68 in EGCG group was also significantly lower than that of HFD group. CONCLUSION: EGCG attenuated inflammation by decreasing the content of macrophages, interfered the toll‐like receptor 4 mediated inflammatory response pathway, thus, improving insulin signaling in adipose tissues.